Neurodireito da memória: a fragilidade da prova testemunhal e de reconhecimento de pessoas - Mariana Suzart Paschoal Ferreira (2019)
The view traditionally held by common sense is that the human brain is like a camcorder, which stores images and clips that, when needed, will be retrieved. However, studies of judicial psychology and neuroscience indicate that brain functioning does not follow this idea. New technologies have allowed the brain machinery to be unraveled without the need for invasive experiments. Thus, it is necessary to investigate the failures in memory, natural and adaptive processes of the human being, but which have serious implications on judicial evidence based on the reliability of memory, that is, testimonial testimony and recognition of people. It is sought, through the judicial evidence, an approximation with what happened, since a total correspondence is unfeasible, in the case of past facts not experienced by the judge. However, projects such as the Innocence Project United States have been demonstrating in practice the high incidence of judicial errors involving such probative species. In this context, it is important to analyze the main mistakes made by the legal operators in the collection of testimonial evidence and the recognition of persons, as well as the techniques for increasing the accuracy of memories that have the ability to fight them, namely the double blind. , the cognitive interview and Self Administered Interview (SAI) in written and oral modalities. It is noteworthy that although countries such as the United States, England, Australia and Canada have already made significant advances in terms of legislative and practical changes to adapt their probative procedures to the findings of forensic psychology, Brazil makes little or no effort to study these methods.